What is needed in future drug treatment research? A systematic approach to identify gaps on effectiveness of drug treatment from the EMCDDA. (February 2015) - Ferri, Marica; Bo, Alessandra; Amato, Laura; Guedes, Inês Correia; Esteves, Carla Sofia; Wiessing, Lucas; Oliver, Sandy; Hickman, Matthew; Davoli, Marina
Abstract There is a perceived global need to bridge the existing gap between researchers and other stakeholders to make research more helpful and to realign "the mismatch between what clinical researchers do and what patients need". The EMCDDA carried out a pilot analysis to explore the gaps in research on treatment for drug dependence as indicated by systematic reviewers of studies on effectiveness of interventions together with a stakeholder's consultation to ensure a broader participation in the definition of research needs. The rough comparisons of the gaps identified by the researchers in the reviews and those suggested by the stakeholders reflect their different perception of research. The reviewers focus on the quality of studies and on how this may impair reaching conclusive evidence, while the stakeholders are more concerned by the management of effective interventions and by the needs of specific patients. With this exercise, the EMCDDA wants to contribute to the broader debate on how to translate evidence into action and it offers a possible way to support decision makers to set the health research agenda.